2021
DOI: 10.3390/cancers13102406
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Complete Response after Biological Downstaging in Patients with Hepatocellular Carcinoma: XXL-Like Prioritization for Liver Transplantation or “Wait and See” Strategy?

Abstract: The XXL trial represents the first prospective validation of “biological downstaging” in liver transplantation (LT) for hepatocellular carcinoma. The aim of this study was to compare the Padua downstaging protocol to the XXL protocol in terms of downstaging failure rates and patient outcome. A total of 191 patients undergoing aggressive surgical downstaging and potentially eligible for LT from 2012 to 2018 at our center were retrospectively selected according to XXL trial criteria. Unlike the XXL trial, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In selected patients with cirrhosis, liver transplantation (LT) represents the gold standard treatment for non-resectable HCC tumors [ 23 ]. The HCC selecting criteria for LT are constantly expanding [ 70 , 71 ], and nowadays, HCC represents the leading indication for LT [ 72 , 73 ]. In this scenario, MILS emerges as a transformative factor that could impact access to LT for HCC in two distinct scenarios: primary LT and salvage LT.…”
Section: Does Mils Increase the Probability Of Primary Or Salvage Liv...mentioning
confidence: 99%
See 1 more Smart Citation
“…In selected patients with cirrhosis, liver transplantation (LT) represents the gold standard treatment for non-resectable HCC tumors [ 23 ]. The HCC selecting criteria for LT are constantly expanding [ 70 , 71 ], and nowadays, HCC represents the leading indication for LT [ 72 , 73 ]. In this scenario, MILS emerges as a transformative factor that could impact access to LT for HCC in two distinct scenarios: primary LT and salvage LT.…”
Section: Does Mils Increase the Probability Of Primary Or Salvage Liv...mentioning
confidence: 99%
“…This proves to be an effective down-staging/downsizing strategy for HCC, potentially paving the way for subsequent LT. The Padua Liver Transplantation Centre’s experience attests to the success of this aggressive approach, achieving down-staging in an impressive 88% of HCC patients—a proportion significantly surpassing that observed in the XXL study, which relied solely on radiological locoregional treatments [ 71 , 74 ].…”
Section: Does Mils Increase the Probability Of Primary Or Salvage Liv...mentioning
confidence: 99%
“…Downstaging is performed for the purpose of reducing tumor volume to within the LT indication criteria for patients whose HCC stage is outside the LT indication criteria. Downstaging HCC to within the LT indication criteria (morphological downstaging) is a means for performing LT, but its true purpose is to reduce the risk of recurrence after LT (biological downstaging) by selecting HCCs with low biological aggressiveness that have few recurrences after LT [ 56 ]. Since the allocation criteria in many countries were based on the Milan criteria, there are many reports of downstaging from outside the Milan criteria to within the Milan criteria.…”
Section: Downstaging Of Hepatocellular Carcinoma For Liver Transplant...mentioning
confidence: 99%
“…They reported that the LT group did better than the control group in both overall survival and tumor event-free survival. On the other hand, regarding the necessity for LT when complete radical treatment is performed by locoregional therapy, Vitale et al [ 56 ] reported comparable results in cases in which complete biological downstaging could be achieved and maintained by strong locoregional therapy to those in the LT group. They concluded that their data strongly support the current allocation system in Italy in which there is no priority in cases obtaining CR by downstaging.…”
Section: Downstaging Of Hepatocellular Carcinoma For Liver Transplant...mentioning
confidence: 99%
“…Studies have demonstrated how using downstaging techniques like TACE, hepatic artery infusion chemotherapy, combined chemo-radiotherapy, SBRT, and TARE (selective internal radiotherapy) can help transplant patients with intermediate stage HCC [30]. The true purpose of downstaging HCC to within the liver transplantation indication criteria (morphological downstaging) is to reduce the risk of recurrence after liver transplantation (biological downstaging) by selecting HCCs with low biological aggressiveness that have few recurrences after liver transplantation [31]. This has led to liver transplantation being included as a possible curative strategy in selected patients with intermediate stage HCC based on tumour biology in the updated Barcelona Clinic Liver Cancer (BCLC) staging and treatment algorithm 2022 [32 ▪▪ ].…”
Section: Downstaging Patients With An Intention Towards Liver Transpl...mentioning
confidence: 99%